2023
DOI: 10.3390/cancers15245746
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Outpatient versus Inpatient Administration of CAR-T Therapies on Clinical, Economic, and Humanistic Outcomes in Patients with Hematological Cancer: A Systematic Literature Review

Doris K. Hansen,
Yi-Hsuan Liu,
Sandip Ranjan
et al.

Abstract: Although chimeric antigen receptor (CAR)-T cell therapies are typically administered in the inpatient setting, outpatient administration is rapidly expanding. However, there is limited summarized evidence comparing outcomes between outpatient and inpatient administration. This systematic literature review aims to compare the safety, efficacy, quality of life (QoL), costs, and healthcare resource utilization (HCRU) outcomes in patients with hematological cancer who are administered CAR-T therapy in an outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…The findings of our study highlight key challenges faced by outpatient CAR T centers, notably: limited institutional capacity, the need for multidisciplinary teams, and the need for protocols for CAR T complications. This is supported by 2 recent articles that have highlighted similar findings to the current study with regard to key drivers of outpatient administration of CAR T for hematologic cancers (predictability of AEs, reduced healthcare burden, and patient quality of life), limiting factors (financial and caregiver support), and best practices (dedicated infrastructure, close monitoring of patients, and patient and caregiver education) ( 24 , 42 ). An expert roundtable also described the importance (in all administration settings) of close patient monitoring, financial and caregiver support considerations, and collaboration across multidisciplinary teams in the administration of CAR Ts for patients with RRMM ( 44 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The findings of our study highlight key challenges faced by outpatient CAR T centers, notably: limited institutional capacity, the need for multidisciplinary teams, and the need for protocols for CAR T complications. This is supported by 2 recent articles that have highlighted similar findings to the current study with regard to key drivers of outpatient administration of CAR T for hematologic cancers (predictability of AEs, reduced healthcare burden, and patient quality of life), limiting factors (financial and caregiver support), and best practices (dedicated infrastructure, close monitoring of patients, and patient and caregiver education) ( 24 , 42 ). An expert roundtable also described the importance (in all administration settings) of close patient monitoring, financial and caregiver support considerations, and collaboration across multidisciplinary teams in the administration of CAR Ts for patients with RRMM ( 44 ).…”
Section: Discussionsupporting
confidence: 89%
“…The current study also highlighted the critical logistical challenges faced by some patients in securing lodging during the 30-day period following outpatient CAR T administration. This aligns with findings from a systematic literature review that identified logistical considerations (e.g., caregiver support, lodging in close proximity to the treatment center) as an important element to consider when administering CAR Ts in an outpatient setting ( 24 ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations